(untitled) (Eureka Journal of Physical and Chemical Research, 2026)
Partial primary tooth agenesis is a congenital dental anomaly that may significantly impact craniofacial development, occlusion, and psychosocial well-being in pediatric populations. The purpose of this study was to evaluate long-term outcomes of different treatment strategies and assess the effectiveness of orthodontic and prosthetic interventions in children and adolescents with partial tooth agenesis. A cohort of 180 patients aged 6–18 years was followed over a period of 5–10 years. Clinical, radiographic, and patient-reported outcomes were analyzed, including arch symmetry, occlusal stability, masticatory efficiency, esthetic satisfaction, and complication rates. Results indicated that early interceptive orthodontic treatment combined with timely prosthetic rehabilitation significantly improved functional and aesthetic outcomes. Patients who received comprehensive multidisciplinary management demonstrated higher satisfaction and fewer complications compared to those with delayed or isolated interventions. These findings underscore the importance of early diagnosis, individualized treatment planning, and long-term follow-up in managing pediatric patients with tooth agenesis.